Finding Baba Yaga : a short novel in verse - Yolen, Jane (Tom Doherty Associates, 2018)
In this contemporary poetic retelling of the iconic myth, a teenage girl fleeing an abusive home takes refuge in the woods with a fairy-tale witch.